(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
Hyperphosphatemia and secondary hyperparathyroidism are common complication of CKD lead to significant morbidity. Dietary restriction of phosphorus is limited by the need to provide adequate protein,estimated at roughly 1.0-1.2g protein per kg body weight in most ambulatory patients. Therefore, most of the patient with CKD require an Exogenous Phosphate binder to prevent hyperphosphatemia. 68 patients of CKD (III-V) not on renal replacement therapy were prospectively evaluated in the department of Nephrology, SSMCH & MH, and Dhaka from Jan 2010 Dec 2011 to see the effect of calcium acetate & Calcium Carbonate as phosphate binder. Patients were subdivided into two equal groups, Group A (received calcium acetate, 667 mg BD) Group B (received calcium carbonate, 1250 mg BD). Both the group were matched for age, sex, BMI & renal function. All patients were withdrawn from any phosphate binder and calcitriol 2 weeks ago & restricted to high protein (0.8 gm/day) & phosphate containing diet. After a wash out period, group A had taken calcium acetate and group B had taken calcium carbonate. All the biochemical parameters (S. PO, S. Ca++, S.Creatinine & iPTH) were estimated at O month, 1st month, 2nd month & 3rd month. One month after intervention showed that serum calcium and serum phosphate were significantly reduced in acetate group than those in calcium carbonate group (P=0.03 & P=0.01). 2nd month after intervention calcium acetate group showed significant reduction of calcium in comparison to calcium carbonate group (P<0.001) & serum phosphate of calcium acetate group decreased further & its difference with calcium carbonate group was significant (P=0.001). At the end of 3rd month calcium acetate group shows a considerable reduction of serum calcium as such there was significant difference between the groups with respect to the variables (P=<0.001). Serum phosphate of calcium acetate group also decreases faster causing a much wider difference with that of calcium carbonate group (P=0.005). After end of the study iPTH decreased proportionately in both groups & serum creatinine was not significantly in either group J. Dhaka National Med. Coll. Hos. 2016; 22 (01): 37-41